Aspects of the transdermal permeation and analysis of betamethasone 17-valerate - Smith, Eric W (Rhodes University, Faculty of Pharmacy, Pharmacy, 1988)
The current world-wide interest in transdermal drug delivery makes the prospect of valid in vitro diffusion cell methodology highly attractive. A new laboratory diffusion cell has been designed and constructed based on theoretical principles and practical permeation reports surveyed in recent literature, and has been applied to the monitoring of betamethasone 17-valerate permeation. The cell performance has been validated with respect to hydrodynamic mixing efficiency and temperature of the receptor phase. The steady-state permeation of this corticosteroid has been monitored through various synthetic and animal membranes in order to select the most appropriate media for in vitro study. The permeation of betamethasone 17-valerate has been monitored from various types of commercial and extemporaneously prepared semisolid topical formulation (cream, lotion, ointment and scalp application), through silicone membrane, human and weanling pig stratum corneum, and full thickness hairless mouse skin, and these in vitro results have been compared to data from in vivo blanching assays, using the same formulations, in an attempt to correlate the findings. This experimental methodology has necessitated the development of ancillary analytical techniques. A column-switching high-performance liquid chromatographic method has been developed for the rapid on-line clean-up and analysis of betamethasone 17-valerate contained in the various topical formulations, which minimizes sample handling and extraction procedures. The method has been modified for the analysis of this corticosteroid in the isopropyl myristate receptor phase used in the in vitro permeation experiments, and scintillation counting of tritium-labelled water has been used to verify the integrity of the animal membranes. The comparison of in vitro permeation and in vivo blanching results indicate good correlation of the data in certain instances. The closest correlations have been observed when the human stratum corneum has been used in vitro and these results are compared to data from the occluded mode of the blanching assay. The results of the porcine and murine media have also correlated with the human in vivo data, whereas the silicone membrane appears applicable only in certain in vitro experiments. The results indicate that valid, comparative percutaneous absorption data may be obtained in vitro by using a well designed, validated diffusion cell system.
Keywords: Transdermal medication; Skin absorption; Dermatologic agents